A televisão no ciberespaço - Capanema, Letícia Xavier de Lemos (2009)
This study identifies some characteristics of the television in cyberspace, understood as the space of interconnected network of computers. As known, the television of the XXI century crossed the boundaries of traditional analog devices, to reside, also, in other platforms, such as those based on computer systems. Given the expansion of television and the sum of their properties to the computer, this study questions the TV specificity in cyberspace, and, therefore, what are the characteristics of this new TV. This master's thesis aims to investigate television products in the cyberspace, trying to understand aspects of the reform of television in this environment, and identify elements to its own procedure. For so, television formats in the Internet and digital TV are highlighted, as the search corpus. First, the study elaborates a brief reflection on past and current expectations regarding the future of television, approached in works of fiction and scientific realities. Such reflection serves as reference to understand contemporary expectations related to digital technology. Aiming to contextualize, in the theoretical field, the current television, this work recovers theories of specificity and periodizations of television, as well as those theories that deal with the convergence of media and processes of hybridization. The concept of additive media of Janet Murray and the theory of remediation of Jay Bolter and Richard Grusin are essential to analyze reforms of television in cyberspace. Finally, the research basis on properties of new media - those already erected by Lev Manovich, as those defined by Janet Murray - to analyze and identify characteristics of the mediation of television in the cyberspace. The conclusions of the research allow classifying the current television moment as a period of intense experiments. These experiments involve the application of computational logic and processes in television production, transforming and expanding the definition of television